2021
DOI: 10.1016/j.jbc.2021.100328
|View full text |Cite
|
Sign up to set email alerts
|

Probing the structure and function of acyl carrier proteins to unlock the strategic redesign of type II polyketide biosynthetic pathways

Abstract: Type II polyketide synthases (PKSs) are protein assemblies, encoded by biosynthetic gene clusters in microorganisms, that manufacture structurally complex and pharmacologically relevant molecules. Acyl carrier proteins (ACPs) play a central role in biosynthesis by shuttling malonyl-based building blocks and polyketide intermediates to catalytic partners for chemical transformations. Because ACPs serve as central hubs in type II PKSs, they can also represent roadblocks to successfully engineering synthases capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 130 publications
0
18
0
Order By: Relevance
“…However, swapping either the AcpP helix II or the N -terminal sequence through helix II with the ACT region led to a significant loss in secondary structure ( Figure S15 and Table S4 ). Given that the helical nature of ACPs are a conserved structural feature that is thought to guide its functional interactions within the synthase, 7,48 the loss of structure is likely a key driver for its loss of ability to bind to FabF.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, swapping either the AcpP helix II or the N -terminal sequence through helix II with the ACT region led to a significant loss in secondary structure ( Figure S15 and Table S4 ). Given that the helical nature of ACPs are a conserved structural feature that is thought to guide its functional interactions within the synthase, 7,48 the loss of structure is likely a key driver for its loss of ability to bind to FabF.…”
Section: Resultsmentioning
confidence: 99%
“…The conformationally dynamic nature of the Ppant arm is thought to play a critical role in their versatility within a given synthase ( Figure 2 ). 79…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental and theoretical studies have confirmed that the PPant group, 18 the α2 helix, 19 and the α3 helix (acting as a conformational 'gatekeeper'; Figure 1b) 20 are all crucial in recognition of PKS and fatty acid synthase (FAS) ACPs 21 by their enzymatic partners. 22 In the actinorhodin system, the labile post-assembly octaketide substrate may be partially protected by actACP 23 whilst being transported to the actKR. 1 The actACP shuttle binds to one monomer of the homotetrameric actKR, whereupon 1 is unsheathed 1 into its active site, which is characteristically narrow and restrictive.…”
Section: Scheme 1 Formation Of Cyclized Octaketide 2 (A) and Subsequent Reactions (B) Amentioning
confidence: 99%
“…In this work, we combine protein-protein docking, molecular dynamics (MD) simulations, 2D protein-NMR spectroscopy and hybrid quantum mechanics / molecular mechanics (QM/MM) simulations to obtain detailed information on actKR -actACP binding and actKR -octaketide interactions: our aim is to provide a unified picture of actKR structure and function and address the lack of fundamental knowledge on type II PKSs. 1,17,22 Materials and Methods Protein-protein Docking. Rigid docking calculations of actKR-NADPH and apo actACP were performed using the Bristol University Docking Engine (BUDE), 41 with GPU acceleration.…”
Section: Scheme 1 Formation Of Cyclized Octaketide 2 (A) and Subsequent Reactions (B) Amentioning
confidence: 99%